Oral Burkitt's lymphoma associated with human immunodeficiency virus - Rafaela Maia Cardoso Almendra; Graziele Beanes da Silva Santos; Natália Nascimento Odilon; Leonardo Francisco Provedel de Souza; Viviane Almeida Sarmento; Luiza Cavalcante Fadul; Luciano Espinheira Fonseca Júnior (Editorial Ciencias Médicas, 2017)
Introduction: Burkitt's lymphoma is an aggressive form of B cell lymphoma generally diagnosed in children and young adults. This tumor has three variants: African (endemic), American (sporadic), and immunodeficiency-associated. Objective: present a case of Burkitt's lymphoma that manifested as a tumor mass in the upper right maxillary region of a patient with AIDS treated at Professor Edgar Santos University Hospital in Salvador, Bahia, Brazil. Clinical case: a male 20-year-old HIV-positive patient was referred from another hospital with a possible odontogenic infection that persisted after drainage and antibiotic therapy. The patient presented a tumor growth in the upper right gingival mucosa. After biopsy, histopathological findings were suggestive of Burkitt's lymphoma. An immunohistochemical panel was positive for CD20 and Bcl6 and negative for CD3, Bcl2, and terminal deoxynucleotidyl transferase antibodies. The Ki67 expression level was 80 %. The final diagnosis was immunodeficiency-associated Burkitt's lymphoma. The patient was successfully treated with cytoreductive chemotherapy (cyclophosphamide, doxorubicin, vincristine, and prednisone), followed by high-dose methotrexate, cyclophosphamide, doxorubicin and vincristine, alternating with high-dose cytarabine, ifosfamide and etoposide. No signs of recurrence have been noted during the follow-up period. Conclusions: Burkitt's lymphoma is an aggressive neoplasia with a rapidly progressing clinical course. Therefore, differential diagnosis from other benign oral diseases is of great importance.